Bridging Mental Health Gaps in Underserved Communities: A Systematic Review of Digital Technologies and Agronursing as Complementary Interventions - Aristawati, Evy; Cahyono, Bagus Dwi; Huda, Nurul; Aditya, Ronal Surya; Rahmawati, Apriana (Journal of Rural Community Nursing Practice, 2025)
Background: The integration of digital mental health technologies presents transformative opportunities for addressing service gaps in underserved and resource-limited areas. Purpose: The objective was to identify, evaluate, and summarize peer-reviewed studies that explored both opportunities and challenges associated with digital mental health interventions in rural, remote, and resource-limited settings. Methods: This systematic review synthesizes evidence from 10 peer-reviewed studies to evaluate the effectiveness, accessibility, and challenges of implementing telemedicine, mobile health (mHealth), SMS-based interventions, and digital platforms across diverse global contexts. Result: Findings reveal that digital tools significantly improve access to care by overcoming geographic barriers, reducing stigma, and enabling remote treatment delivery. However, challenges such as inadequate digital infrastructure, data privacy concerns, and limited digital literacy hinder equitable adoption. The study further explores agronursing defined as therapeutic agricultural practices as a complementary, community-centered approach to supporting mental well-being, particularly in rural settings. Conclusions: By combining technological innovation with nature-based therapies, this review highlights pathways toward more inclusive and sustainable mental health service delivery. These insights are critical for policymakers and healthcare providers aiming to address global mental health disparities through context-sensitive solutions.